Large scale poly(vinyl alcohol-co-ethylene)/TiO2 hybrid nanofibrous filters with efficient fine particle filtration and repetitive-use performance. Issue 107 (15th October 2015) - Liu, Ke; Xiao, Zuan; Ma, Pengfei; Chen, Jiahui; Li, Mufang; Liu, Qiongzhen; Wang, Yuedan; Wang, Dong
Abstract : A high-yielding nanofiber-based filtration material with excellent performance was developed and provides a promising way to control the severe air pollution at present. Abstract : Severe air pollution results in a great demand for high-yielding nanofiber-based materials with excellent filtration performance. In this work, PVA- co -PE/TiO2 hybrid nanofibrous filters on PP nonwoven supports were prepared on a large scale via a melt phase separation and suspension coating technique. The hybrid nanofibers doped by TiO2 nanoparticles have a diameter in the range from about 50 nm to 300 nm. With increasing fiber coverage density, the average pore size of the hybrid nanofibrous filter media declines from 10 μm for PP nonwoven to less than 500 nm. Compared to pristine PVA- co -PE nanofibrous filter media, the hybrid nanofibrous filters exhibit much higher filtration efficiency and lower pressure drop, which further induces an increased quality factor by about 167%. This is mainly attributed to the enhanced electrostatic absorption between hybrid nanofibers and NaCl aerosol nanoparticles caused by the polarity of TiO2 . Besides, the secondary factor is the slightly weakened direct-interception ability of the filter media with increased pore size. Furthermore, it was found that a multilayered-structure was generated by the cyclic swilling–drying handling. This structure results in the steadily increasing particle-collection capability and quality factor of PVA- co -PE/TiO2 hybrid nanofibrous filter media, implying its superiority in the application as an air filter media with high filtration efficiency and repetitive-use performance.